UNIFIKASI DALAM PLURALISME HUKUM TANAH DI INDONESIA (REKONSTRUKSI KONSEP UNIFIKASI DALAM UUPA) - MUHAMMAD BAKRI (Fakultas Hukum Universitas Udayana, 2008)
After the enforcement of The Basic Agrarian Law, land law in Indonesia has the character of unification, meaning that only one land law applied that is national land law. Enforcing one particular land law at various society as in Indonesia, can generate injustice. Therefore, the Decision Of People Consultative Assembly Number of IX/MPR/2001 Section 4 letter c opens the opportunity of pluralism in unification sounding: Respecting law supremacy by accommodating varieties in law unification. What is meant by